Penggunaan Biji Pepaya Sebagai Koagulan Alami Dalam Pengolahan Air Limbah Domestik - Syardah Ugra Al Adawiyah; Faryda Veronica Lamma Koly (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
One of the chemical contaminants in domestic wastewater is phosphate. High phosphate levels in water can cause algae bloom (eutrophication), which leads to a decrease in oxygen concentration in the water body and subsequently results in the death of aquatic organisms. Papaya seeds contain natural polymers in the form of proteins that act as natural polyelectrolytes, helping to reduce chemical contaminants in waste. This study aims to determine the most effective dose of papaya seed coagulant (Carica papaya L.) for lowering phosphate levels, turbidity and pH of domestic wastewater. An experimental method was used with varying sizes and doses of papaya seed coagulant: 70, 80 dan 90 mesh, and doses: 0.5 grams, 1 gram, 1.5 grams, and 2 grams, tested using a jar test. The reduction in phosphate levels in domestic wastewater was measured with a UV-Vis spectrophotometer. The results showed the treatment of domestic wastewater for reducing phosphate levels using papaya seed (Carica papaya L.) coagulant can be achieved by adding 2 grams of coagulant with a particle size of 90 mesh. Under these conditions, the phosphate levels decreased from 2.1529 mg L⁻¹ to 0,1907 mg L⁻¹, with an efficiency of 88.96%. According to the Domestic Wastewater Quality Standard No. 68 of 2016, the maximum allowable phosphate concentration is 0.2 mg L⁻¹, making the research results close to the established standard. Additionally, turbidity decreased from 86.55 NTU to 26.40 NTU, while the pH level increased from 6.5 to 6.9. This study suggests that papaya seeds could be a cost-effective, sustainable alternative for domestic wastewater treatment, especially in reducing phosphate contamination and helping maintain water quality